Global Monitoring Report 2013 : Rural-Urban Dynamics and the Millennium Development Goals - World Bank; International Monetary Fund (Washington, DC: World Bank, 2013)
The Global Monitoring Report 2013: Rural-Urban Dynamics and the Millennium Development Goals examines rural-urban disparities in the achievement of the Millennium Development Goals (MDGs) and how urbanization, if managed well, can contribute to the attainment of these goals. The report provides information about the differences in progress toward the MDGs across geographical areas and recognizes that urban populations are better off than their rural brethren. However, unfettered urbanization can cause migrants and the urban poor to end up in slums where attainment of the MDGs lags.